Dinamika Alih Fungsi Lahan Perkebunan Teh di Jawa Barat: Perspektif Sosial, Ekonomi, dan Lingkungan - Labida, Lulu; Djuarsa, Febby Firdian; Achmad, Mubarik; Ernah, Ernah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Land use change in tea plantation areas in West Java is a complex phenomenon influenced by the interaction of various social, economic, and environmental factors. This study aims to identify the driving factors behind tea land conversion through a systematic literature review of reputable scientific publications from 2020 to 2024. Thematic analysis shows that generational shifts among farmers, weak local institutions, short-term economic incentives, market price pressures, ecological degradation due to monoculture practices, and climate change are the dominant drivers of land conversion. The interaction of social, economic, and environmental factors creates reinforcing feedback loops that accelerate land use change. This phenomenon results in trade-offs between short-term income gains and the loss of strategic ecosystem services. The findings highlight the importance of evidence-based spatial planning policies, land conservation incentives, local community empowerment, and the integration of spatial mapping and ecosystem valuation. This study recommends future research to develop predictive models of land conversion using spatial technology and quantitative ecosystem valuation methods to support sustainable tea plantation land protection policies in West Java.